Centralpladser i romersk jernalder - Hansen, Astrid Skou (Kuml, 2003)
Centres in the Roman Iron Age During the last 10-15 years, a number of new sites from the Roman Iron Age have been found throughout Southern Scandinavia. These sites are different from the standard agricultural settlements of the period, in that they contain structures and objects testifying to greater resources and to contacts with areas more deeply affected by Roman culture. These centres have cleared the path for a new understanding of Iron Age society. It is now commonly accepted that the centres of the Roman Iron Age were the predecessors of the structure which formed the basis of the kingdom – and subsequently the state – of Denmark during the Viking Age. On this basis one might expect that there would be a thoroughly tested codex of how to describe what happened during this development in society. However, this is not the case. The purpose of this article is to try to outline the advantages and disadvantages of some of the terms and concepts used in this field of research. And at the same time to explain what it is that happens in the Roman Iron Age that is of interest in relation to the formation of the state in the Viking Age. The most rudimentary definition of a centre is that it is a site that shows signs of having a function which has been of importance to people in an area larger than the territory of the site itself. There are, of course, different levels on which a site can be a centre. Some sites may have been of importance only to the nearest neighbouring sites, while others may have dominated an entire region. This article primarily concerns the centres which have been of importance to a relatively large group of people scattered over a large area. This is due to the fact that these sites are easier to recognise as centres. They are the ones containing the most exceptional and varied material, including inter alia Roman imports. The first theory to be evaluated is proposed by Charlotte Fabech and Jytte Ringtved in the book Produksjon og samfunn. This theory advocates that to obtain an overview of the geography of power during the Iron Age it is necessary to identify which sites were normal agricultural units and which were centres on a regional or super-regional level. This involves dividing the sites into social and political levels based on the archaeological evidence. This is done by identifying specific types of items and dividing them into levels based on the level of expertise needed to produce them (fig. 1) (tables 1-2). The second theory to be evaluated is proposed by Margrethe Watt in an article concerning the site Sorte Muld in the book Fra Stamme til Stat 2. It is similar to the first theory, in that it relies on dividing the evidence into 3 categories. In this case common material, material containing evidence of crafts and material of an exceptional character (fig. 2) (table 3). The third theory is very different from the two first ones, both with regard to method (how to establish whether a site is a centre), and, to a lesser degree, with regard to concept (what is a centre?). This theory is proposed by Kent Andersson in the book Samfundsorganisation og Regional Variation, Norden i romersk jernalder og folkevandringstid. The hypothesis is that by analysing gold objects it is possible to find out where they have been manufactured, and thereby to find the centres from which they originate. The fourth theory is proposed by Bertil Helgesson in the book Centrala Platser- Centrala Frågor. This is very different from the other theories, in that it does not operate with different levels of centres. Instead it operates with four aspects of centrality in Iron-Age society. The four aspects are: phenomenon, function, localisation and person. According to Ulf Näsman and the fifth theory, there are two questions which are important when working with centres. These questions are: – Centre, yes – but central in what? – Centre, yes – but in what way? These two questions are important, since many of the problems concerning the centres change aspect depending on which interpretation is chosen (fig. 3). In general terms, it is not desirable to divide the material into categories which are as tight as the theories proposed above, because it is not certain that there were abrupt divisions between different levels of centrality. This is a matter of purely subjective judgement and as such it is neither desirable nor possible to force the archaeological material into this type of frame – if it is an objective and complex interpretation of Iron Age society which is the goal. On the other hand, there is nothing wrong with using a tight classification to create an overview of the volume and geographical distribution of the material. But then what happens when the centre is identified? Is the task of the archaeologist completed? Or should we try to “peel off” another layer to try to find out what lies behind the way the centres appear, and why they evolved in the first place? It is a fact that in what is now Denmark, a central power existed in the Roman Iron Age. A central power strong enough to organise markets and attract imported luxury goods. But how this central power was organised is still an open question. It is not possible to determine whether there was always a single site that controlled the exchange of products, cult and military activities, and other central aspects of society in an area controlled by a local power-force. On the other hand, there is nothing to indicate that this was not the case. For instance the situation in the Gudme area indicates that a figure of power located on the Gudme site was responsible for both the market at Lundeborg, the cult activities indicated by the place-names, and the exceptionally rich burials at Møllegårdsmarken. On other sites, however, the situation is more ambiguous. In Sorte Muld there are traces of craft production, trade and cult activities, but there are no cemeteries containing graves with imported goods and no signs of large dwellings or halls to indicate that this was where the local elite lived. It must be presumed, however, that this was the place where the elite established themselves, on the basis of the dense culture layers and the rich metal-detector finds. But at a site where such evidence had not been preserved, it would not have been possible to determine whether there had actually been a power-force present in the shape of a powerful individual. As a conclusion on the questions of what it is that is central and what a centre really is, the easiest thing to do would be to follow the proposals already made and form a hierarchy, with one site as the most central, redistributing items such as imported goods to sites which were less central. However this is not the most correct approach. If one attempts to apply the theories above, it is important that they are used as an inspiration and to complement each other rather than to prove each other wrong. If one starts by using the first theory to obtain an overview of the level on which a site is situated, on the basis of the finds, and then tries to interpret the phenomena and the functions present by using the fourth theory, finishing by fitting the evidence into a larger perspective using theory no. 5, it should be possible to form a composite picture of a single site, based on both the overview from the first theory and the greater depth of analysis from theories 4 and 5. Astrid Skou Hansen Afdeling for Forhistorisk Arkæologi Aarhus Universitet Moesgård